FACTORS THAT INFLUENCE WHISTLEBLOWING INTENTIONS VILLAGE GOVERNMENT OFFICIAL - Yesi Mutia Basri; Ferty Riarni; Nur Azlina; M. Haykal Daditullah Indrapraja (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2020)
The study investigates the factors that influence village officials to have an interest in whistleblowing. Organizational commitment, rewarding, idealism ethical orientation, relativism and machiavellian ethical orientation are used as factors that influence the interest of village officials to do whistleblowing. The population in this research is the entire officials of the village government who worked in district Kelayang, Indragiri Hulu Regency. The sampling technique in this research is to use incidental sampling. A total of 60 village officialses participated in this study, which consisted of village heads, village secretaries. regional executor and technical executive. The data analysis technique used is multiple regression. The results of hypothesis testing that is: organizational commitment and idealism ethical orientation effect on interest to do the whistleblowing but reward, relativism ethical orientation and machiavellian nature has no effect against the interest to do the whistleblowing.This research contributes to reducing the occurrence of fraud committed by village officials.